PENGANTAR MENUJU TEOLOGI SANTO YOSEPH: MUNGKINKAH DINAMAKAN DENGAN YOSEFOLOGI? - Philipus Benitius Metom (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2021)
This paper contains a theological study of Saint Joseph in the context of filling in the year of Saint Joseph which Pope Francis announced in the apostolic letter of Patris Corde. Two questions were raised at the start of this essay: Why is there no discipline of dogmatic theology that deals with theology of Saint Joseph? Is it possible for the theological study of Saint Joseph to be called Josephology, as Mariology and Christology have also been recognized? After basic biblical accounts, teachings and thoughts of the Magisterium of the Church, the pastoral appeal of the liturgy and the possibility of the discipline of Josephology, four points are finally found. First; This paper is called an introduction to Saint Joseph's theology because its establishment as a theological discipline is in the Magisterium of the Church, the holder of infallibility in the teaching of the faith. Second; as an introduction, this paper has only elaborated only a part or less of it, and it is proven that it has not completely explored all knowledge of Saint Joseph, because his new exposition of the biblical basis and a number of the teachings of the Pope, while theological thinking in the tradition of the Church fathers has not been given a place. Third; If it is recognized that the existence of Josephology or Saint Joseph's theology, then this discipline cannot be categorized in the dogmatic theology group of sciences but may be recognized as contextual theology, or rather it is called Saint Joseph's contextual theology. As a scientific discipline, Saint Joseph's theology, or Josephology, describes the observance of faith and piety of Saint Joseph's behavior which God engages in the work of salvation. Fourth; the way to pursue the theology of Saint Joseph or Josephology, not only by reading books of knowledge about the excellence and uniqueness of this father of the faithful, but also by persevering in devotional prayer with him.